STRATEGI PEMASARAN BERBASIS BUDAYA DAN SYARIAH: PENGGUNAAN SIMBOL JAWA DALAM BRANDING PRODUK MUSLIM: Culture and Sharia-Based Marketing Strategies: The Use of Javanese Symbols in Muslim Product Branding - Saripermanik Budayanti (Business, Accounting and Management Journal, 2025)
This study aims to explore the effectiveness of marketing strategies that integrate Javanese cultural visual identity with sharia principles in the Muslim product industry, particularly batik. Amidst the currents of globalization and the dominance of Middle Eastern Islamic symbolism, there is an urgency to understand how local wisdom can synergize with halal labels to attract local consumers. This study uses a qualitative case study approach in batik industry centers in Central Java. Data were collected through in-depth interviews, participant observation of branding materials, and document analysis. The results show that: (1) The combination of Javanese symbols (such as Gunungan, Kawung motifs) with calligraphy or halal labels creates a perception of "Islamic Javanese Authenticity" that increases consumer trust; (2) This branding strategy is not merely a promotional tool, but a manifestation of the values ​​of mutual cooperation adopted by the industrial cluster, where competition is reduced by the ethics of mutual assistance; and (3) The integration of Islamic values ​​and local culture creates a sustainable competitive advantage that is difficult for imported products to imitate. This study makes a theoretical contribution to the Islamic marketing literature by proposing that congruence between cultural and religious symbols strengthens brand loyalty in collectivist societies.